Mathematical Literacy Ability Reviewed from Cognitive Style of Students on Mind mapping Learning Model with Constructivism Approach - Hairunisah, Hairunisah; Mulyono, Mulyono; Walid, Walid (Universitas Negeri Semarang, 2020)
This purpose of this study was to know the quality of learning and mathematical literacy ability reviewed from the students’ cognitive style in learning by using Mind mapping Learning Model with Constructivism approach. The method in this study used a mixed method with concurrent embedded design. This research conducted on VII grade students of SMP Negeri 40 Semarang in the academic year 2017/2018. To collecting data was done by tests, interviews, and observation sheets. The quality of learning reviwed by few stages were planning, implementation and assessment. The result of test matematical literacy ability were analyzed by quantitatively with a mean test, classical completeness test, proportion difference test and mean difference test. Students were grouped based on their cognitive style characteristics consisting of field dependent and field independent which chose four students to be interviewed. The results of the study showed; (1) learning with mind mapping model with constructivism approachs on mathematical literacy ability is good qualified which were indicated by; (a) learning tools that have been compiled are valid, (b) the level of implementation in the learning process is a good category; and (c) the assessment of learning outcomes takes place effectively (2) The mathematical literacy ability with field dependent cognitive style were able to master four indicators from the six indicators of mathematical literacy abilities and the other two indicators include representation and reasoning and argumentation have been less able to be mastered. Students with a field independent cognitive style were able to master all indicators of mathematical literacy ability and did not have constraints on indicators.